Pengaruh penambahan santan kelapa (Cocos nucifera L.) terhadap karakteristik fisikokimia dan organoleptik velva bit merah (Beta vulgaris L.): Effect of adding coconut milk (Cocos nucifera L.) on the physicochemical and organoleptic characteristics of red beetroot velva (Beta vulgaris L.) - Elen, Sisilia; Handoko, Yoga Aji (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Red beetroot is a type of purplish red tuber with a slightly sweet taste accompanied by an earthy aroma. Several studies on the processing of red beet products have been carried out, one of which is Velva. The Velva product still has shortcomings because it still has a strong unpleasant taste and aroma, so it is necessary to add other ingredients such as coconut milk. Coconut milk contains high levels of galactomannan and phospholipids which can improve unpleasant taste and aroma. This research aimed to know the effect of adding coconut milk and determine the best concentration of coconut milk on the physicochemical and organoleptic characteristics of red beetroot. This research used RAK 6 treatments and 4 repetitions with varying concentrations of added coconut milk (0%, 20%, 40%, 50%, 60% and 80%). Sample parameters in this study include: overrun, melting power, TPT, fiber content, betacyanin content, fat content, and organoleptic (color, aroma, taste, texture). The results of the research showed that the addition of coconut milk to red beetroot velva with different concentrations influenced the overrun, melting power, TPT, fiber content, betacyanin content, fat content, and organoleptic properties produced. Based on these characteristics, BS4 is the best treatment, producing an overrun of 6.26%, melting power of 18 minutes, TPT of 18Â°brix, crude fiber of 17.71%, betacyanin content of 2.75Âµg/gram, and fat content of 9.67%. Additionally, the entire panel liked the color, aroma, taste, and texture of the BS4 treatment. The resulting color is red guava, fragrant coconut milk aroma, a delicious and savory taste, and a smoother velva texture.